HUBUNGAN PENGETAHUAN PP NO 33 TAHUN 2012 DENGAN SIKAP PEMBERIAN ASI EKSLUSIF DI PUSKESMAS GAMPING I KABUPATEN SLEMAN TAHUN 2025 - Salsabila, Salsabila; Tri Hapsari Listyaningrum (Journal of Innovation Research and Knowledge, 2025)
Breast milk is a very important source of nutrition for babies and their development. Breast milk contains vitamins, proteins, fats, carbohydrates, and other essential minerals. Colostrum, which is the first breast milk to come out, is rich in nutrients and antibodies that protect babies from infection. Exclusively breastfeeding during the first six months of life can prevent disease, save lives, and ensure healthy growth. In DI Yogyakarta Province, the Exclusive Breastfeeding rate reached 76.3%, the third highest according to the Ministry of Health of the Republic of Indonesia in 2023, this is an achievement for the fulfillment of the Exclusive Breastfeeding target in DI Yogyakarta, while the figure in Sleman Regency reached 88.10%, the highest from Bantul and Kulon Progo Regencies which occupied the second and third positions in 2023. Objective: This study aims to determine the Relationship between Knowledge of Government Regulation No. 33 of 2012 and Exclusive Breastfeeding at the Sleman Regency Health Center Method: This study uses a Descriptive correlation design with a cross sectional approach Sampling in this study is Nonprobability Sampling with Purposive Sampling Technique The sample in this study is mothers who have children aged 7-12 months who give breast milk in the work area The health center totals 65 people. Results: The results of the Chi-Square statistical test showed a relationship between knowledge and exclusive breastfeeding with a p-value of 0.00 out of 65 percent showed mothers with good knowledge and providing Exclusive Breastfeeding amounted to 42 people (85.7%) while those who were knowledgeable but did not provide Exclusive Breastfeeding amounted to 7 people (14.3%). Mothers with a poor level of knowledge and exclusive breastfeeding amounted to 1 person (6.3%), while those with a poor level of knowledge and gave exclusive breastfeeding amounted to 15 people (93.8%). Conclusion: There is a relationship between knowledge and Exclusive Breastfeeding at the Health Center, Sleman Regency. Suggestion: Seeing that there are still many mothers who have misunderstood breastfeeding, such as the assumption that breastfeeding alone is not enough or the provision of MP-ASI early, education needs to be focused on these things